Evaluation of Passenger Terminal Service Facilities using SWOT Analysis at Tanjung Emas Class I Port, Semarang - Rusmiyanto, Dedy; Wahyudi, Slamet Imam; Adi, Henny Pratiwi (ASTONJADRO, 2025)
This study aims to evaluate passenger terminal service facilities at Tanjung Emas Port, Semarang, using the SWOT Analysis method (Strengths, Weaknesses, Opportunities, Threats). This evaluation aims to identify the strengths, weaknesses, opportunities, and threats faced by passenger terminals in providing optimal service to users. The results of the analysis show that the main strength lies in adequate infrastructure and security systems, such as effective CCTV. However, weaknesses related to emergency response facilities and limitations in the dissemination of cargo policies need to be improved. Opportunities to improve service quality can be realized through the use of modern technology, while the biggest threats arise from increased passenger volumes and regulatory changes. Recommendations include improving emergency response facilities, utilizing CCTV for real-time monitoring, and providing better transportation facilities for passengers. The implementation of this strategy is expected to be able to improve the quality of passenger terminal services in the future.